"Stream of Consciousness" and Otar Chiladze's Novels - Tamar Gegeshidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
Otar Chiladze is one of the Georgian writers who developed Georgian prose on the basis of numerous theories and doctrines to better present reality, characters of heroes, and their own worldviews in literary works produced in the interdisciplinary environment of the 20th century. Correspondingly, almost all main trends characteristic of the 20th-century literature can be seen in Chiladze's novels. These include clear-cut Mythologism or Remythologisation, elements of "Magic Realism" characteristic of the Latin American prose, deep psychologism - an attempt to understand the spiritual world of humans, which the author managed to show, taking into account the theories of depth psychology by Sigmund Freud and Carl Gustav Jung. His works in the genre of new historic prose are also noteworthy. The characteristic manner of writing should also be mentioned. Narration proceeds from the subjective perspective and attempts are periodically made to go deep into not only the conscious, but also the unconscious of heroes by means of the method of the "stream of consciousness".